Content analysis of Escherichia coli in Sliced Yellowfin Tuna - Asrin Mosii; Femy Sahami; Sitti Nursinar (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2019)
The purpose of this study is to determine Escherichia coli bacterial content in chunks of yellowfin tuna (Thunnus albacores) sold in Central Market Gorontalo. This study uses descriptive analysis method which gives an idea as carefully as possible about an individual, state, symptom, or a particular group. Based on observations of the total MPN Coliform samples A, B and C have MPN coliform exceed ISO standards for quality and food safety requirements of fresh fish, ie 24.00 MPN / g. Test EMBA (Eosin Methylene Blue Agar (EMBA) indicates that the Tuna Yellowfin positive for the bacterium Escherichia coli with colors that are characterized by green metalic. Pieces of tuna sold in the central market town Gorontalo safe to eat at 08:00 am, while at 10:00 am and 12:00 am bacterial content becomes a lot more. The longer the fish are displayed at table without any effort to maintain the quality of the fish, the more the bacteria contained in the fish. Keywords: E. coli; yellowfin tuna; Thunnus albacores; pieces; content analysis.